2013
DOI: 10.1007/s00027-013-0309-4
|View full text |Cite
|
Sign up to set email alerts
|

Sediment dynamics in the subaquatic channel of the Rhone delta (Lake Geneva, France/Switzerland)

Abstract: With its smaller size, well-known boundary conditions, and the availability of detailed bathymetric data, Lake Geneva's subaquatic canyon in the Rhone Delta is an excellent analogue to understand sedimentary processes in deep-water submarine channels. A multidisciplinary research effort was undertaken to unravel the sediment dynamics in the active canyon. This approach included innovative coring using the Russian MIR submersibles, in situ geotechnical tests, and geophysical, sedimentological, geochemical and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 58 publications
2
44
0
Order By: Relevance
“…These fans can extend over thousands of kilometers (Schwenk et al, 2003). Lake Baikal, Russia (e.g., Back et al, 1999) and Lake Geneva, Switzerland (Corella et al, 2014) have leveed subaqueous channels. Sediment flushing events from Xiaolangdi Dam, China, document continuous long runout turbidity currents (Figure 1a; e.g., Li, 2011;Xie et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These fans can extend over thousands of kilometers (Schwenk et al, 2003). Lake Baikal, Russia (e.g., Back et al, 1999) and Lake Geneva, Switzerland (Corella et al, 2014) have leveed subaqueous channels. Sediment flushing events from Xiaolangdi Dam, China, document continuous long runout turbidity currents (Figure 1a; e.g., Li, 2011;Xie et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The present work was part of the larger éLEMO project that examined several chemical, physical, biological and geological characteristics of the lake (this issue). Of particular interest to our study are the sediment deposition processes in the Rhone delta, which are well detailed in Corella et al (2013), and discusses the interplay between erosion and sedimentation along the main canyon (henceforth called the 'active' canyon) extending from the river flow. We measured sediment dissolved CH 4 concentrations along transects in three of the subaquatic canyons of the delta and estimated production and diffusion rates in each.…”
Section: Introductionmentioning
confidence: 99%
“…Corella et al (2014) dove with the MIRs into the subaquatic Rhône canyons and investigated their sediments. The analysis of the sediment cores revealed that erosion processes control the sediment dynamics in the proximal canyon floor while sedimentation dominates on the levees.…”
Section: Results and Summarymentioning
confidence: 99%